Matter & interactions - Chabay, Ruth W.; Sherwood, Bruce A. (2015)
Matter and Interactions offers a modern curriculum for introductory physics (calculus-based). It presents physics the way practicing physicists view their discipline while integrating 20th Century physics and computational physics